Motivasi Belajar Siswa dalam Meningkatkan Pembelajaran Bola Voli Passing Bawah di Kelas VIII SMPN 1 Pondoksalam Purwakarta - Ade Herawati; Abduloh Abduloh; Citra Resita (Universitas Singaperbangsa, 2021)
This research is the motivation to learn students in improving volleyball under passing learning through class VIII SMPN 1 Pondoksalam Purwakarta. The purpose of this study was to see how student learning motivation in improving skills in learning volleyball under passing. Researchers chose this topic because there were students when learning volleyball under passing was not serious enough to make the scores obtained by students not optimal. In this study, researchers used a qualitative approach. Data were collected through interviews. The research choose participants was taken from grade VIII SMP Pondoksalam and the researcher has get 5 students. Researchers chose this object because there are be founded many students who are still not focused on learning volleyball under passing at school. The sampling technique used is Provosive Sampling in which the data source sampling technique is taken with certain considerations. In this technique, the consideration used is the person who is considered to know best about what we expect or as the ruler so that it will make it easier for researchers to explore the object or situation. The instruments used in this study were divided into 3, namely: observation, new interviews, and documentation studies. Some stages are carried out during the research, namely: the stages, the stages of the stages, and the member check stages. For data analysis using data reduction, data presentation, and drawing conclusions/verification. The results of this study indicate that motivation affects learning outcomes. Intrinsic motivation and extrinsic motivation have an important role in enhancing learning. Encourage and learning needs, hopes, dreams, and learning make students have a desire to learn that arises from within themselves. Meanwhile, rewards in learning, interesting learning, and a conducive environment provide external stimulation for students to take part in learning.